Asthma research in Europe: a transformative agenda for innovation and competitiveness. Issue 5 (2nd May 2017) - Papadopoulos, Nikolaos G.; Androutsopoulou, Aggeliki; Akdis, Cezmi; Dahlén, Sven-Erik; Djukanovic, Ratko; Edwards, Jessica; Garcia-Marcos, Luis; Johnston, Sebastian L.; Kupczyk, Maciek; Martin, Thomas R.; Myles, David; Palkonen, Susanna; et al.
Asthma is highly prevalent, often starting in infancy and persisting throughout life, and is associated with high morbidity and burden. It is a major global health challenge with growing impact, affecting more than 300 million people worldwide and at least 10% of all Europeans [1]. Furthermore, it is the most prevalent long-term condition in children [2]. Approximately 5–10% of asthma cases are so severe that current treatments do not work, and over five million people in the European Union (EU) fall into this category. Asthma research in Europe: a transformative agenda for innovation and competitiveness http://ow.ly/YssR30aNG9h